A Study of the Play Aphai Nuraraj through the Concept of Patriarchy - Keawseesod, Nattaphong; Klomsuk, Suppharoek; Suthanaphinyo , Suphakkhathat (Manutsat Paritat: Journal of Humanities, 2026)
This article aims to study the play Aphainuraj through the concept of patriarchy, employing Michel Foucault’s discourse theory and Roland Barthes’ concept of myth as analytical frameworks. The study applies content analysis to the 1985 Fine Arts Department edition of Aphainuraj. The findings reveal that the text reflects a patriarchal social structure by positioning male characters, particularly King Aphainuraj, as the center of power in his roles as ruler, husband, and arbiter of social legitimacy. Female characters, meanwhile, are devalued and portrayed as subordinates, objects of male desire, and self-sacrificing women within the idealized framework of the “virtuous woman.” Furthermore, patriarchal discourse legitimizes the exercise of power and violence against women, while myths surrounding the ideal lady and the self-sacrificing mother normalize female submission as a virtue. The study demonstrates that Aphainuraj not only reflects but also perpetuates ideas concerning gender, power, and patriarchal values in Thai society.